2006
DOI: 10.1177/0363546505285583
|View full text |Cite
|
Sign up to set email alerts
|

Elongation and Structural Properties of Meniscal Repair Using Suture Techniques in Distraction and Shear Force Scenarios

Abstract: Meniscal repair with horizontal suture techniques can withstand elongation due to shear forces more effectively than can vertical mattress sutures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 45 publications
1
37
1
Order By: Relevance
“…However, this significant difference of elongation at the repair site between horizontal and vertical outside-in suture techniques did not influence the stiffness and the maximum load of the corresponding repaired meniscus construct in the shear compared with the axial distraction force scenario, 20 which is consistent with our results. Contrary to Zantop et al, 20 we could demonstrate a markedly and significantly reduced stiffness of the Ethibond 2.0 vertical as well as the horizontal loops in the shear compared to the tensile load scenario. Conflicting stiffness and the unequal peak levels of the load to failure in both studies may be explained by the variable test protocol (cyclic vs noncyclic), suture technique (outsidein vs inside-out), test speed (12.5 mm/s vs 5 mm/min), test temperature (room vs body temperature), and animal model (porcine vs bovine).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, this significant difference of elongation at the repair site between horizontal and vertical outside-in suture techniques did not influence the stiffness and the maximum load of the corresponding repaired meniscus construct in the shear compared with the axial distraction force scenario, 20 which is consistent with our results. Contrary to Zantop et al, 20 we could demonstrate a markedly and significantly reduced stiffness of the Ethibond 2.0 vertical as well as the horizontal loops in the shear compared to the tensile load scenario. Conflicting stiffness and the unequal peak levels of the load to failure in both studies may be explained by the variable test protocol (cyclic vs noncyclic), suture technique (outsidein vs inside-out), test speed (12.5 mm/s vs 5 mm/min), test temperature (room vs body temperature), and animal model (porcine vs bovine).…”
Section: Discussioncontrasting
confidence: 99%
“…Zantop et al 20 have investigated the structural properties of a horizontal and vertical meniscal suture repair technique in an axial distraction and shear force scenario under cyclic loading. Interestingly, they found that meniscal repair with a horizontal suture technique can withstand elongation caused by shear forces more effectively than a vertical suture technique, which may be important for limitation of meniscal tissue displacement at the meniscal repair site during the healing process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that meniscal repair using horizontal sutures sustained less elongation than vertical sutures when subjected to shear forces [7,23]. Reduced elongation or displacement during healing is vital to the success or failure of arthroscopic meniscal repair.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have looked at suture technique and wound strength. In a study by Zantop et al (2006), it was found that meniscal repair with horizontal suture techniques can withstand elongation due to shear forces more effectively than can vertical mattress sutures. Poole et al (1984) found that with laparotomy wounds, the simple interrupted technique was unaffected by suture tension but was generally inferior to the running stitch in terms of wound-bursting strength.…”
mentioning
confidence: 99%